SISTEM INFORMASI PENJUALAN DENGAN MENERAPKAN TEKNOLOGI RFID - Dwi Oktarina (RJOCS (Riau Journal of Computer Science), 2017)
Many supermarket sales transactions have advanced information systems. The information system that has been running this time theor supermarket implement information systems that run on a self-service supermarkets in general, by applying the system scan the barcode on the cash register to identification goods. System barcode has some weaknesses that the barcode is used to identify all items similar, less effective way because of all the goods using the identity code of the same goods so that unable to identify the goods in detail, it can cause difficulties at the time of introduction of the goods to a purposes. otherwise use the barcode system can also be effect number of fairly long queue at the time of purchase that quite a lot during the crucial hours or crowded. This is caused because the cashier must Scanning items one by one. This study utilizestechnology Radio Frequency Identification(RFID) in the information system designed to overcome the problem in  supermarket. For analysis of the system, is used method of System Development Life Cycle (SDLC)to Microsoft SQL 5.0 and Microsoft Visual Basic 6.0. By using the technology of Radio Frequency Identification (RFID) identification of goods can be carried out in detail and this technology makes it possible to scan items at once without doing the touching because this technology uses the wave beam to read or identify goods.